2017
DOI: 10.1080/10942912.2016.1274906
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acids and flavonoids profiles of extracts from edible wild fruits and their antioxidant properties

Abstract: In this study, the total phenolic, total flavonoids, phenolic compounds, the mineral content, and antioxidant activity of fruit extracts of seven wild species (Crataegus monogyna Jacq., Prunus spinosa L., Rosa canina L., Hippophaë rhamnoides L., Rubus fruticosus L., Prunus padus, Cornus mas L.) were investigated. The results indicated significant differences (p < 0.05) in the total phenolics and total flavonoids content, between the seven analyzed species. These ranged from 184.69 to 727.29 mg GAE/100 g FW and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 33 publications
5
86
5
Order By: Relevance
“…Many researchers have recently paid special attention to fruits of Cornelian cherry ( C. mas L.) [ 18 , 19 , 20 ], that are rich in biologically-active compounds, iridoids in particular, and thereby exhibit potential therapeutic properties [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have recently paid special attention to fruits of Cornelian cherry ( C. mas L.) [ 18 , 19 , 20 ], that are rich in biologically-active compounds, iridoids in particular, and thereby exhibit potential therapeutic properties [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They postulated that a strong synergistic effect of phenolics, flavonoids and ascorbic acid, as well as other uninvestigated bioactive compounds, could be responsible for the DPPH scavenging activity. Cosmulescu et al (2017) concluded that the antioxidant activity of Rosa spp. fruits was linked to individual phenolic compounds rather than to total phenolic content.…”
Section: Dpph Scavenging Activitymentioning
confidence: 99%
“…There is a current growing interest in natural sources with a high content of bioactive compounds [1]. Among these natural sources, plant products (fruits, berries, leaves, flowers, etc.,) with antioxidant properties are increasingly being applied in the food, cosmetic and pharmaceutical industries as effective remedies to counteract the harming actions of free radicals and to stop oxidant processes that cause different pathological conditions [2]. Such natural antioxidants are very useful as substitutes for synthetic antioxidants, the use of which is being restricted because of their potential risks for health and side-effects [3].…”
Section: Introductionmentioning
confidence: 99%